2011
DOI: 10.1007/s00586-011-1840-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of spinal decompression in cauda equina syndrome presenting late in developing countries: case series of 50 cases

Abstract: The purpose of this study is to find the clinical outcome of decompression of Cauda Equina presenting late in the course of disease. There were 33 males and 17 females with average age of 48 years, ranging from 25 to 85 years. All patients presented to us with a fully developed Cauda Equina syndrome (CES). All of them presented late with mean delay of 12.2 days. Time interval between bladder and bowel dysfunction and admission to hospital varied from 1 to 35 days. The average follow-up was 34.5 months, ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…This results in a shorter duration of CES complaints (patient delay) as well as a shorter time to decompression (doctor delay), even though outcome is poor (due to the extent of the lesion). Patients that show reasonable outcome when decompression is delayed by weeks [31], probably had a favourable anatomical lesion and more gradual onset of complaints. Since it is not (yet) possible to distinguish the group with the favourable conditions from the group with the less favourable conditions at the time of presentation (since, e.g., the exact correlation of clinical presentation and degree of canal obstruction on imaging is not yet known), it is necessary to decompress every CES patient as soon as possible, to create the best chances for fair recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This results in a shorter duration of CES complaints (patient delay) as well as a shorter time to decompression (doctor delay), even though outcome is poor (due to the extent of the lesion). Patients that show reasonable outcome when decompression is delayed by weeks [31], probably had a favourable anatomical lesion and more gradual onset of complaints. Since it is not (yet) possible to distinguish the group with the favourable conditions from the group with the less favourable conditions at the time of presentation (since, e.g., the exact correlation of clinical presentation and degree of canal obstruction on imaging is not yet known), it is necessary to decompress every CES patient as soon as possible, to create the best chances for fair recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly quoted time frame in which decompression of diskogenic cauda equina syndrome should take place is within 48 hours from symptom onset. 26 In this study, decompression of the cauda equina was delayed by a mean of 12.2 days, with a delay of 35 days in one patient. 23,25 The data on late decompression were provided by a study performed in India in a setting in which spine surgeons are not routinely available.…”
Section: Surgical Interventionmentioning
confidence: 59%
“…They suspected that further improvement would occur, as indeed the paper by Dhatt et al [5] showed in his review some 2 years ago. They looked at the outcome of spinal decompression in cauda equina syndrome presenting late, in developing countries in 50 patients.…”
Section: Review Articlesmentioning
confidence: 91%